Evaluating the impact of type 2 diabetes mellitus on CYP450 metabolic activities: protocol for a case–control pharmacokinetic study. Issue 2 (8th February 2018) - Gravel, Sophie; Chiasson, Jean-Louis; Dallaire, Suzanne; Turgeon, Jacques; Michaud, Veronique
Abstract : Introduction: Diabetes affects more than 9% of the adult population worldwide. Patients with type 2 diabetes mellitus (T2DM) show variable responses to some drugs which may be due, in part, to variability in the functional activity of drug-metabolising enzymes including cytochromes P450 (CYP450s). CYP450 is a superfamily of enzymes responsible for xenobiotic metabolism. Knowledge must be gained on the impact of T2DM and related inflammatory processes on drug metabolism and its consequences on drug response. The aim of this study is to characterise the activity of CYP1A2, CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP2E1 and CYP3A4/5 in T2DM versus non-T2DM subjects following the administration of a cocktail of probe drug substrates. Methods and analysis: This single-centre clinical study proposes the first detailed characterisation of T2DM impacts on major CYP450 drug-metabolising enzyme activities. We intend to recruit 42 patients with controlled T2DM (A1C≤7%), 42 patients with uncontrolled T2DM (A1C>7%) and 42 non-diabetic control subjects. The primary objective is to determine and compare major CYP450 activities in patients with T2DM versus non-diabetic subjects by dosing in plasma and urine probe drug substrates and metabolites following the oral administration of a drug cocktail: caffeine (CYP1A2), bupropion (CYP2B6), tolbutamide (CYP2C9), omeprazole (CYP2C19), dextromethorphan (CYP2D6), chlorzoxazone (CYP2E1) and midazolam (CYP3A4/5). Secondary objectives will evaluate the influence of variables such as glycaemia, insulinaemia, genetic polymorphisms and inflammation. The value of an endogenous biomarker of CYP3A activity is also evaluated. The first patient was recruited in May 2015 and patients will be enrolled up to completion of study groups. Ethics and dissemination: Approval was obtained from the ethic review board of the CHUM research centre (Montreal, Canada). Trial registration number: NCT02291666.